436. Assessing SARS-CoV-2 Infection among Persons Experiencing Homelessness — Atlanta, GA, 2020. (31st December 2020) - Yoon, Jane C; Morris, Sapna; Schmit, Kristine; Hernandez, Alfonso; Montgomery, Martha; Ko, Jean; Boyd, Andrew T; Buff, Ann; Flowers, Nicole; Jamison, Calla; Mosites, Emily; Paulin, Heather; et al.
Abstract: Background: Persons experiencing homelessness (PEH) often do not have sufficient resources to practice public health interventions. PEH may reside at overcrowded shelters, have poor access to health care, and often suffer from significant co-morbid conditions. In this study, we describe prevalence of COVID-19 amongst PEH and homeless service staff in Atlanta, Georgia, as well as demographic data, underlying conditions, and symptoms. Methods: In response to the COVID-19 pandemic in Atlanta, PEH and homeless service providers were offered PCR testing for SARS-CoV-2 via nasopharyngeal, nasal mid-turbinate, and oropharyngeal swabs. Shelters identified as having a higher number of COVID-19 infections underwent re-testing 3–4 weeks after initial testing. Demographic information was collected, and individuals were screened for symptoms and underlying conditions. Results: A total of 2, 294 PEH and 544 staff underwent SARS-CoV-2 PCR testing from April 8 - May 6, 2020. 24 homeless shelters were included in this study. The majority of individuals were male (66.3% sheltered, 85.5% unsheltered, 55.3% staff), and 2, 192 of 2, 838 (78.3%) persons identified as black. Approximately half of individuals had no known underlying conditions (51.5% sheltered, 47.7% unsheltered, 55.5% staff). Cardiovascular disease was the most frequently reported condition (32.0%), followed by chronic lung disease (14.8%). In total, 45 of 2, 823 (1.6%) individuals had detectable PCR results for SARS-CoV-2, including 35 of 1, 666 (2.1%) sheltered clients, 3 of 614 (0.5%) unsheltered clients, and 7 of 543 (1.3%) staff. Among individuals with detectable SARS-CoV-2, 5 of 20 (25%) reported at least one symptom in the last week. Most shelters (16 of 24) had at least one individual with detectable SARS-CoV-2. The prevalence of SARS-CoV-2 in the majority of shelters (19 of 24) was < 3%, with a median prevalence of 0.2% across all shelters. Upon retesting 4 shelters with a higher number of COVID-19 infections, only 3 individuals from 2 shelters tested positive out of 357 total retested (0.8%). Conclusion: We identified a low prevalence of SARS-CoV-2 infection among PEH in Atlanta, which was influenced by a pre-emptive testing strategy. Continued vigilance is necessary to limit spread in this vulnerable population. Disclosures: All Authors : No reported disclosures